Profile of an occupation – chimney sweep - Schambeck, Arne [Verfasser] (My University, 2026)
"It’s not just about sweeping chimneys any more: Chimney sweeps are highly qualified skilled workers. They check heating and ventilations systems for safety, ensure that environmental standards are met, and provide advice on climate-friendly technologies. This profile describes the entire scope of the training occupation modernised in 2025 and presents the development of trainee figures." (BIBB-Doku)
Keywords: S 6.4 Dienstleistungsberufe; 370; Schornsteinfeger; Berufsbild; Tätigkeitsmerkmal